THE ROLES OF TRADITION AS AN IDEA FOR THE DOCUMENTARY FILM ‘MAPPADEKKO’ WITH EXPOSITORY DIRECTING STYLE - Annisa, A.Mulya; Harsakya, Cahya Surya; Kurniawan, Donie Fadjar; Nugrahaning Widhi, Dwi Putri (ISI Press Institut Seni Indonesia Surakarta, 2024)
The Mappadekko Documentary Film is a form of cultural preservation that raises the issue of the role of traditional leaders in preserving a nearly extinct annual tradition in Camba District. Mappadekko is a form of gratitude to God Almighty for the success of planting rice. The narrative structure of this film employs the 5W+1H framework for storytelling. The film employs an expository directing approach. The expository directing approach primarily documents the involvement of traditional leaders in the Mappadekko tradition through the use of narration and interviews. This style prioritizes informal shooting activities to convey the message directly to the audience, minimizing the potential for other interpretations. The Mappadekko documentary film conveys a message that urges the audience, particularly the younger generation, to prioritize cultural awareness and preservation